Associations of exposure to blood heavy metal mixtures with Toxoplasma infection among U.S. adults: a cross-sectional study - Zhou, Jing; Xing, Chen; Chen, Yuting; Shen, Jilu (Frontiers in Public Health, 2024)
IntroductionResearch increasingly links environmental exposure to toxic metals with health risks, yet the effect of combined metal exposure on Toxoplasma infection remains underexplored. This study investigates the relationship between concurrent heavy metal exposure and Toxoplasma infection in adults.MethodsWe analyzed data from 10,746 adults aged 20–80 from NHANES, with 1,869 positive for Toxoplasma gondii IgG. The study assessed associations between lead (Pb), cadmium (Cd), and mercury (Hg) with Toxoplasma infection risk using single-metal logistic regression, RCS analysis, WQS regression, and qgcomp models.ResultsEach metal showed an independent association with Toxoplasma infection risk. Pb had a non-linear association, while Hg had a linear one. Analysis of multiple metals indicated a positive correlation between heavy metal exposure and infection risk, particularly in younger and middle-aged adults, with Pb showing the strongest link.DiscussionOur findings reveal a significant association between heavy metal exposure and Toxoplasma infection risk, especially in younger demographics, with lead being a key factor. This highlights the importance of understanding environmental metal exposure’s impact on public health and informs the development of prevention strategies.